2008
DOI: 10.1136/sti.2007.028324
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of consistent condom use among female commercial sex workers in the Democratic Republic of Congo: implications for interventions

Abstract: The risk perception bias associated with non-paying partners, time as a commercial sex worker and age should be taken into account when planning interventions targeting CSW. Access to condoms and VCT should be improved because they are likely to impact on behaviour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
53
1
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(73 citation statements)
references
References 27 publications
15
53
1
4
Order By: Relevance
“…Condom use with regular non-paying partners and boyfriends were reported to be lower and less consistent than condom use with paying partners. This finding is consistent with other studies reporting similar outcomes in condom use by FSWs with regular or non-paying clients (Johnson, Haefton, Fishbeina, Kasprzykb, & Montanob, 2001;Kayembe et al, 2008;Stoebenau, Hindin, Nathanson, Rakotoarison, & Razafintsalama, 2009;Voeten, Egesah, Varkevisser, & Habbema, 2007;Wang et al, 2007). This trend could compromise ongoing efforts to address the HIV epidemic in sub-Saharan Africa.…”
Section: Discussionsupporting
confidence: 82%
“…Condom use with regular non-paying partners and boyfriends were reported to be lower and less consistent than condom use with paying partners. This finding is consistent with other studies reporting similar outcomes in condom use by FSWs with regular or non-paying clients (Johnson, Haefton, Fishbeina, Kasprzykb, & Montanob, 2001;Kayembe et al, 2008;Stoebenau, Hindin, Nathanson, Rakotoarison, & Razafintsalama, 2009;Voeten, Egesah, Varkevisser, & Habbema, 2007;Wang et al, 2007). This trend could compromise ongoing efforts to address the HIV epidemic in sub-Saharan Africa.…”
Section: Discussionsupporting
confidence: 82%
“…Subsequent studies in Congo have just shown information about condom availability (which is not nationally ensured) (Bosmans, Cikuru, Claeys, & Temmerman, 2006), condom use (Laga et al, 1994), determinants (Kayembe et al, 2008;Ntumbanzondo, Dubrow, Niccolai, Mwandagalirwa, & Merson, 2006) and barriers for using condoms (Irwin et al, 1991;Kabamba Mulongo, Schirvel, Mukalay Wa Mukalay, & Dramaix Wilmet, 2011;Kayembe, Fatuma, Mapatano, & Mambu, 2006). A recent cross-sectional study among people attending VCT in a rural area found a very low prevalence of consistent use and a non-significant association, in a bivariate analysis, between any condom use and HIV (Kautako-Kiambi, Ekila, Kama-Lemba, Wumba, & Aloni, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The limited amount of existing research has shown high incidences of unintended pregnancy and a low contraceptive prevalence in this particular group [3][4][5][6] . All studies report that sex workers who do use contraception resort most often to condoms yet the latter are not consistently used in all sex acts 3,[5][6][7][8][9] . FSWs may have difficulties in negotiating the consistent use of condoms with clients, and also may deliberately use condoms with some types of partners (such as casual clients) while deliberately not using condoms with other types of partners (such as emotional partners or regular clients) 10 .…”
Section: Introductionmentioning
confidence: 99%